Growth-dependent and growth-independent translation of messengers for heterogeneous nuclear ribonucleoproteins. - Camacho-Vanegas, O (1997)
The hnRNP A1 transcript has a relatively short 5'- untranslated region (UTR) starting with a pyrimidine tract similar to that of mRNAs encoded by the TOP [terminal oligo(pyrimidine)] genes in vertebrates. Such genes code for ribosomal proteins and for other proteins directly or indirectly involved in the production and function of the translation apparatus. As expected from the role of the pyrimidine tract in the translational regulation of TOP mRNAs, the A1 mRNA is more efficiently loaded onto polysomes in growing than in resting cells. On the other hand, a less stringent regulation with respect to that of other TOP mRNAs is observed, partially due to the presence of multiple transcription start sites within the pyrimidine tract, where transcripts with shorter TOP sequences are less sensitive to regulation. Thus, from the point of view of structural features and translation behaviour the A1 mRNA can be included in the class of TOP genes, suggesting a possible role of A1 in translation. Interestingly, a TOP-like behaviour was observed for hnRNP I mRNA but not for hnRNP C1/C2 and A2/B1 mRNAs, indicating the existence of two classes of hnRNPs with different translational regulation.